2009
DOI: 10.1103/physrevlett.102.218301
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Surface-Bound Oligonucleotide Duplex Inferred from Molecular Dynamics: A Study of Single Nucleotide Defects Using DNA Microarrays

Abstract: Microarray technology uses the sequence dependent hybridization (binding) affinity of surface-bound oligonucleotide strands for the quantification of complex nucleic acid mixtures. In spite of its huge potential in life science and medicine, microarray oligonucleotide hybridization remains far from being understood. Taking advantage of microarray combinatorial possibilities we show that, although surface bound, the hybridization affinities of single-base mismatched oligonucleotides can be derived from first pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 25 publications
1
41
1
Order By: Relevance
“…Δ g init = -4.5 kcal/mol is the duplex initialization free energy [17]. For the binding constant K i ( P , L ), K i ( P , L ) = Z D ( P , L ) taking the totally denatured state, S 0 , as the reference state.…”
Section: Resultsmentioning
confidence: 99%
“…Δ g init = -4.5 kcal/mol is the duplex initialization free energy [17]. For the binding constant K i ( P , L ), K i ( P , L ) = Z D ( P , L ) taking the totally denatured state, S 0 , as the reference state.…”
Section: Resultsmentioning
confidence: 99%
“…The general effect of incomplete probe synthesis on the hybridization of microarrays has been discussed in refs. [49] and [13].…”
Section: Discussionmentioning
confidence: 99%
“…33 This might as well explain the known lower hybridization efficiency, but higher stability, of the duplex for surface tethered oligonucleotides. 31,34,35 Thus, the added strands, in a non-zipped configuration, imply a larger configurational entropy penalty, as the non-zipped strands have short persistence length and the increased number of molecules in the same surface area implies a larger surface stress upon the ssDNA polyelectrolyte swelling. Molecular dynamics simulations of DNA hybridization on surfaces have also shown that the cited non-zipped intermediate states occur during the hybridization process.…”
Section: Resultsmentioning
confidence: 99%